2016
DOI: 10.1371/journal.pone.0147366
|View full text |Cite
|
Sign up to set email alerts
|

Histological Characterization of the Tumorigenic “Peri-Necrotic Niche” Harboring Quiescent Stem-Like Tumor Cells in Glioblastoma

Abstract: BackgroundCharacterization of the niches for stem-like tumor cells is important to understand and control the behavior of glioblastomas. Cell-cycle quiescence might be a common mechanism underlying the long-term maintenance of stem-cell function in normal and neoplastic stem cells, and our previous study demonstrated that quiescence induced by hypoxia-inducible factor (HIF)-1α is associated with a high long-term repopulation capacity of hematopoietic stem cells. Based on this, we examined human astrocytoma tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 49 publications
(66 reference statements)
3
63
0
Order By: Relevance
“…The literature published in recent years has revealed a growing focus on tumour cell dormancy, which is probably one of the main reasons for refractory to targeted or conventional therapies (7)(8)(9)(10). In glioma, the 'peri-necrotic niche' harbouring HIF-1α + quiescent stem-like cells have been proposed as candidates for long-term tumourigenic cells (11). For the enrichment in angiogenesis of upregulated DEGs, it is widely recognized that the extreme proliferation of new blood vessels in GBM is structurally and functionally abnormal and contributes to a hostile microenvironment (low oxygen tension and high interstitial fluid pressure) that selects for a more malignant phenotype with increasing morbidity and mortality (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…The literature published in recent years has revealed a growing focus on tumour cell dormancy, which is probably one of the main reasons for refractory to targeted or conventional therapies (7)(8)(9)(10). In glioma, the 'peri-necrotic niche' harbouring HIF-1α + quiescent stem-like cells have been proposed as candidates for long-term tumourigenic cells (11). For the enrichment in angiogenesis of upregulated DEGs, it is widely recognized that the extreme proliferation of new blood vessels in GBM is structurally and functionally abnormal and contributes to a hostile microenvironment (low oxygen tension and high interstitial fluid pressure) that selects for a more malignant phenotype with increasing morbidity and mortality (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…3,8 A number of studies of perivascular niches have histological or histochemical images. 7,[65][66][67][68][69] Figures 3-5 show the relevant images. The vessels in the center of the perivascular niches have in all four cases a diameter that is too large and walls that are too thick for capillaries.…”
Section: Vessel Type In Perivascular Gsc Nichesmentioning
confidence: 99%
“…The definition of a tumor is a mass of cells that proliferate without relation to pattern or rate of the growth of the part in which it is located. This unlimited cellular growth may lead to the development of malignant properties, including invasion of surrounding tissues and metastasis to other organs [ 44 ]. In this study, we concluded from the following observations that none of the transplanted cells developed into malignant tumors.…”
Section: Discussionmentioning
confidence: 99%